The statement that is true about the equation 3(-y + 7) = 3(y + 5) + 6 is;
Statement A; The equation has one solution, y = 0
The given equation is;
3(-y + 7) = 3(y + 5) + 6
Expanding the brackets gives us;
-3y + 21 = 3y + 15 + 6
-3y + 21 = 3y + 21
Using subtraction property of equality, subtract 21 from both sides to give;
-3y = 3y
Using addition property of equality, add 3y to both sides to give;
-3y + 3y = 3y + 3y
6y = 0
Using division property of equality, divide both sides by 6 to get;
y = 0
Read more about factorization at; brainly.com/question/11000698
The missing statements are;
A. The equation has one solution, y = 0.
B. The equation has one solution, y = -1.
C. The equation has no solution.
D. The equation has infinitely many solutions.
Answer:
1.) Yes
2.) Yes
Step-by-step explanation:
Given that
n = k(k + 7)
If k is a positive integer and n = k(k + 7), is n divisible by 6 ?
(1) k is odd. Yes.
Let assume that k = 3
Then, n = 3(3 + 7)
n = 3 × 10
n = 30.
30 is divisible by 6.
(2) When k is divided by 3, the remainder is 2. That is,
Let k = 5
Then,
5/3 = 1 remainder 2
Substitute k into the equation
n = k(k + 7)
n = 5(5 + 7)
n = 5 × 12
n = 60
And 60 is divisible by 6.
Therefore, the answer to both questions is Yes.
Answer:
9^-3= .0013717421
Step-by-step explanation:
Answer:
the answer is 12
Step-by-step explanation:
it is what it is
Answer:
A.
Step-by-step explanation:
38% = 38/100 = 0.38
A percentage is anything over 100